Youth justice and workforce development in workforce development in Scotland: practice makes better! - Claire Lightowler; David Orr; Nina Vaswani (Scottish Journal of Residential Child Care)
The youth justice workforce includes everyone who comes into contact with, or more broadly whose work affects, children and young people who are, have been or are at risk of being perpetrators or victims of offending (young people tend to be both) (Drake & Henley, 2014).